Pengaruh Etika, Sosialisasi, Dan Denda Pajak Terhadap Kepatuhan Wajib Pajak (Studi Empiris Di Kantor Pelayanan Pajak Pratama Surakarta) - Petrus Kanisius G. Hewen; Sugiarti Sugiarti; Faiz Rahman Siddiq (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2022)
The purpose of this study was to obtain empirical evidence of the effect of tax ethics, taxsocialization, and tax penalties on taxpayer compliance. The population of this study is all SurakartaCity Individual Taxpayers, a total of 1,228 taxpayers, with the number of samples used is 250respondent. Collecting data using primary data sources in the form of a questionnaire compiledwith a five-point Likers scale. The analytical method used is multiple linear analysis. Test the qualityof the data in this study using the R2 test, F test, and t test. the results of this study indicate that thevariables of tax ethics, tax socialization, and tax penalties have a positive effect on individualtaxpayer compliance.